2010
DOI: 10.3109/09553002.2010.518210
|View full text |Cite
|
Sign up to set email alerts
|

Medium-mediated effects increase cell killing in a human keratinocyte cell line exposed to solar-simulated radiation

Abstract: This study has shown that solar radiation toxicity is augmented by cell culture medium due to the presence of riboflavin. Results suggest that exposures performed in phenol red-free medium may serve to increase phototoxic effects if riboflavin is present. Riboflavin-free media is recommended for solar radiation investigations to eliminate concerns regarding riboflavin photosensitisation and nutrient deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
(53 reference statements)
0
16
1
Order By: Relevance
“…Contrasting with earlier studies with HEPES‐supplemented RPMI and normal DMEM‐F12 medium, which identified Rf photo‐conversion as the main causative factor for ROS/RNS formation, this present study data do not support such a strict mechanistic link 15, 25. According to EEM spectra (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrasting with earlier studies with HEPES‐supplemented RPMI and normal DMEM‐F12 medium, which identified Rf photo‐conversion as the main causative factor for ROS/RNS formation, this present study data do not support such a strict mechanistic link 15, 25. According to EEM spectra (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…A constant amount of radicals seems to be formed in situ without involvement of exogenous stress factors such as light, and to a different extent in different media formulations. Alternatively, it is possible that serum components (as were supplemented to DMEM) act as radical scavengers, which was reported for similar systems 16, 25…”
Section: Discussionmentioning
confidence: 78%
“…The presence of phenol red in the medium was found to significantly reduce the toxicity of riboflavin, however. Exposure in riboflavin-free medium resulted in significantly increased cell survival compared to identical exposure in riboflavin containing medium 21 . It is important therefore to expose in riboflavin free medium.…”
Section: Solar Exposurementioning
confidence: 89%
“…5). Although both RB and riboflavin are phototoxic to cultured cells, 10,29,32 only riboflavin is phototoxic during photo-crosslinking, causing loss of keratocytes by apoptosis and necrosis to the same distance from the anterior surface as UVA penetration. 9,11 Formation of RB/collagen complexes may greatly reduce the amount of free RB available to enter cells, whereas riboflavin, which rapidly diffuses in cornea, 33 enters the keratocytes, where it absorbs UVA and initiates toxicity.…”
Section: Discussionmentioning
confidence: 99%